The Government as Employer - Best, J. C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1961)
SummaryThe author makes a brief historical review of government policy in relation to civil service employees. He then analyses the structures and functions of those bodies which are involved in personnel administration on behalf of the Federal government. The employee organizations are also taken care of by the author. Finally, there is a description of the relations between the two groups and an estimate of their achievements. The author concludes that the Government should decide, in cooperation with its organized employees, to work out a system of bargaining or negotiation.